The Effect of Exclusive Breastfeeding Education on Changes in Knowledge and Attitudes of Toddler Mothers - Peran, Peran; Satriani, Satriani; Joto, Nur Abri; Wiryanto, Wiryanto (Journal of Health and Nutrition Research, 2024)
Optimal breastfeeding practices contribute greatly to the quality of a child's growth and development. Breast milk is considered a golden feeding of nutrients in infants. Mothers have a big role in improving the quality of their children's health. This study aims to determine the effect of exclusive breastfeeding education on the knowledge and attitudes of mothers of toddlers in the working area of the Tiong Ohang Health Centre. The research is a quasi-experiment with a design with a two-group pretest and posttest approach conducted in July 2023 in the working area of the Tiong Ohang Health Center, East Kalimantan, Indonesia. The sample of this study was 36 under five mothers. The data is then collected and then analyzed with the Wilcoxon test. Results show that the effect of exclusive breastfeeding education using leaflet media on increasing knowledge of mothers under five (p = 0.000). There is an influence of exclusive breastfeeding education using brochure media on increasing the knowledge of mothers of toddlers (p = 0.002). There is an influence of exclusive breastfeeding education using leaflet media on changes in the attitudes of mothers under five (p = 0.001). There is no effect of exclusive breastfeeding education using brochure media on changes in the knowledge of mothers under five (0.132). Leaflet media is more effective to use than brochure media. This finding is empirical evidence that nutrition education is needed to continue to be encouraged, especially in remote areas